MANDIEK ANAK AS PERFORMANCE AT SALAREH AIA - Sathotho, Surya Farid (Institut Seni Indonesia Yogyakarta, 2022)
Mandiek anak is rituals as part of baralek gadang. Although baralek gadang is a marriage ritual known in the West Sumatra region or Minangkabau, but mandiek anak is only known in the Nagari Salareh Aia region. This ritual aims to show society the social status of the organizer of the mandiek anak. Theatre anthropology shows how mandiek anak can be seen as a performance. In this approach, mandiek anak is treated as a performance that can be analyzed the forming elements. The method used to conduct research is purposive sampling. The resulting description is analytical to the phenomenon found. With a comprehensive description, it can be seen that the elements of mandiek anak as a performance can be identified. The performance elements in scripts, players, audiences and places look real. Mandiek anak scripts are all rules that ensure the passage of mandiek anak in an orderly and smooth manner. Players and spectators have intense interactions and a real-looking performance venue. The results of this study expect to show how mandiek anak as performance has a particular form that makes it can be passed down to the supporting community. Keywords: mandiek anak, teater antropology, performance